O cinema como instrumento de propaganda política integralista (1932-1937) - Nascimento, Giceli Warmling do (2016)
This study aims to gather information on how the Ação Integralista Brasileira (1932-1937) used the cinema to spread its political propaganda. It was sought to gather information to make it possible to understand how the AIB viewed cinema using it?s own press, as well as information about the films and their producers. The existence of these films, likewise information on these productions were in the ?Cinemateca Brasileira?. Thus, the work is structured to point out how the movement perceived cinema, and how the film producing structure was conceived. It was also sought to present the filmmakers who filmed the AIB and its productions. Some elements in these productions were mentioned, as well as the range of AIB propaganda through film. This work tries to make a contribution to the collection of information on the use of film by AIB, allowing more historiographical research to be carried out